Understanding resource choice at the transition from foraging to farming: An application of palaeodistribution modelling to the Neolithic of the Konya Plain, south-central Anatolia, Turkey. (August 2018) - Collins, Christina; Asouti, Eleni; Grove, Matt; Kabukcu, Ceren; Bradley, Lee; Chiverrell, Richard
Abstract: The role of the environment in shaping agricultural origins is still not fully understood, despite a century of debate on this topic. Comparison of the expected prevalence of a resource in the landscape with actual archaeological presence of the same resource can provide a metric for assessing resource choice in prehistory. However, the palaeoenvironmental data that would allow resource choice to be evaluated in this way are rarely available. Species Distribution Modelling (SDM) techniques allow independent palaeoenvironmental datasets to be computed, which when compared to actual species' presence at sites as attested by archaeological datasets, can provide data on resource choice. Following recent calls for SDM to be applied more widely in archaeological contexts, we outline a simple method for predicting the presence of plant species in prehistory using modern analogues and palaeoclimatic datasets. These modelled distributions provide an independent dataset for comparison with archaeological data, thus providing a window into human resource choice in prehistory. We outline the method with specific reference to the transition from foraging to farming in the Neolithic of Central Anatolia, but the method could be applied to any period or region. We have used exclusively open source data and provided all code in our online supplementary materials, so that our method can be utilized by researchers interested in human resource choice in any region of the world and any period. Highlights: Species distribution modelling applied to the Neolithic of Central Anatolia. Comparison of modelled distributions of plants with observed archaeological presence allows us to understand resource choice. Results suggest that crop progenitors were abundant in 9th Millennium BC Konya but local foragers chose not to exploit them. Cultural preferences seem to have affected diet choice in the Neolithic of Central Anatolia. Our method can be applied to any region/period and uses entirely open source data.